Distributed AoA-based Source Positioning in NLOS with Sensor Networks - Pere Gimenez-Febrer; Alba Pagès-Zamora; Silvana Silva Pereira; R. López-Valcarce (IEEE International Conference on Acoustics, Speech, and Signal Processing (ICASSP), 2015)
This paper focuses on the problem of positioning a source using angle-of-arrival measurements taken by a wireless sensor network in which some of the nodes experience non-line-of-sight (NLOS) propagation conditions. In order to mitigate the errors induced by the nodes in NLOS, we derive an algorithm that combines the expectation-maximization algorithm with a weighted least-squares estimation of the source position so that the nodes in NLOS are eventually identified and discarded. Moreover, a distributed version of this algorithm based on a diffusion strategy that iteratively refines the position estimate while driving the network to a consensus is presented.
Keywords: compass; wsn